The Comparative Academic Performance of International Students in Australia - Olsen, Alan John; Burgess, Zena; Sharma, Rajeev (International Higher Education, 2006)
International students do just as well as Australian students. This is the key finding from a study of the academic performance of 338,000 full-time students at 22 Australian uni- versities in 2003. The results of the study are important to international education professionals globally at a time when there have been allegations that Australian universities were dropping stan- dards to favor foreign students. The Sydney Morning Herald claimed in June 2005 to have found evidence of quality falling at universities to cater to international students with poor English seeking degrees so as to be accepted for migration. The research proved these allegations to be untrue. Australian students passed 89.4 percent of courses attempted, international students 88.8 percent. The results suggest that in their recruitment of international students Australian universities set their standards at about the right level.